Multi-hop broadcast message dissemination in vehicular ad hoc networks: A security perspective review - Alejandro Galaviz-Mosqueda; Miguel Morales-Sandoval; Salvador Villarreal-Reyes; Hiram Galeana-Zapién; Raúl Rivera-Rodríguez; Miguel Ángel Alonso-Arévalo (International Journal of Distributed Sensor Networks)
Vehicular ad hoc networks have been identified as a key technology for enabling safety and infotainment applications in the context of smart and connected vehicles. In this sense, diverse approaches of multi-hop broadcast protocols have been proposed to collect and disseminate context information through the network. However, before vehicular ad hoc networks applications fulfill their expected potential to connect smart vehicles, several issues must be addressed. Among these issues, those related to security are of particular importance. In this article, the main security issues of broadcast message dissemination in vehicular ad hoc networks are discussed. Moreover, a review of the most relevant threats and proposed solutions to secure broadcast message dissemination in vehicular ad hoc networks is presented and discussed. As mentioned, security is an important topic which has not been fully addressed in vehicular ad hoc networks; therefore, the aim of this article is to introduce security issues and proposed solutions related to three main security concerns associated with the message dissemination process in vehicular ad hoc networks: network access, data consistency, and broadcast protocols.